HIV-Associated Disseminated Histoplasmosis and Rare Adrenal Involvement: Evidence of Absence or Absence of Evidence - Nacher, Mathieu; Alsibai, Kinan Drak; Valdes, Audrey; Abboud, Philippe; Adenis, Antoine; Blaizot, Romain; Blanchet, Denis; Demar, Magalie; Djossou, Félix; Epelboin, Loïc; Misslin, Caroline; Ntab, Balthazar; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Adrenal histoplasmosis and primary adrenal insufficiency are mostly described in immunocompetent patients. This particular tropism is attributed to the presence of cortisol within the adrenal gland, a privileged niche for Histoplasma growth. In French Guiana, disseminated histoplasmosis is the main opportunistic infection in HIV patients. Our objective was to search in our HIV-histoplasmosis cohorts to determine how frequent adrenal insufficiency was among these patients. Between January 1, 1981 and October 1, 2014, a multicentric retrospective, observational study of histoplasmosis was conducted. Patients co-infected by HIV and histoplasmosis were enrolled in French Guiana’s histoplasmosis and HIV database. Among 349 cases of disseminated histoplasmosis between 1981 and 2014, only 3 had adrenal insufficiency (0.85%). Their respective CD4 counts were 10, 14 and 43 per mm3. All patients had regular electrolyte measurements and 234/349 (67%) had abdominal ultrasonography and 98/349 (28%) had abdominopelvic CT scans. None of these explorations reported adrenal enlargement. Overall, these numbers are far from the 10% reports among living patients and 80-90% among histoplasmosis autopsy series. This suggests 2 conflicting hypotheses: First, apart from acute adrenal failure with high potassium and low sodium, less advanced functional deficiencies, which require specific explorations, may have remained undiagnosed. The second hypothesis is that immunosuppression leads to different tissular responses that are less likely to incapacitate the adrenal function. Furthermore, given the general immunosuppression, the adrenal glands no longer represent a particular niche for Histoplasma proliferation.